A Comparative Study of Geometrical Patterns: Escher’s Tessalation and Passura Toraya Ornaments - Andi Baetal Mukadas; Faizal Erlangga Makawi; Jamilah; Muhaemin; Siti Asmaulul Izmi; Hasbi (PT Mattawang Mediatama Solution, 2025)
This research aims to compare the geometric patterns in Passura Toraya and Escher’s Tessalation. The study examines Toraja ornaments created 5.000 years ago from a geometric perspective that is similar to the approach of well-known geometric artist, M. Escher. The research method used is a descriptive qualitative method by collecting data from literature studies and visual observations of Passura Toraya, which are then analyzed using geometrical pattern and basic mathematic shapes. The results of the study show that (1) triangle, square, pentagon, flora, and fauna shapes represent geometric forms with similar tessellation techniques in both Passura Toraya and M.C. Escher's geometric patterns; (2) Passura Toraya has repeated patterns in opposite directions and four sides, as well as 4-fold designs, similar to M.C. Escher's tessellated geometric patterns with the same size as the empty field and 3-fold repetition levels; (3) contrasting colors are characteristic of Passura Toraya, similar to M.C. Escher's designs. Passura Toraya, which was made approximately thousands of years ago, shows the same approach as geometric artist, M. Escher. This demonstrates that Passura Toraya was made with a high level of knowledge, despite being made approximately 5.000 years ago.